Precise radial velocities of giant stars: XIII. A second Jupiter orbiting in 4:3 resonance in the 7 CMa system - Luque, Rafael; Reffert, Sabine; Quirrenbach, Andreas; Wolthoff, Vera (Astronomy and astrophysics, 2019)
We report the discovery of a second planet orbiting the K giant star 7 CMa based on 166 high-precision radial velocities obtained with Lick, HARPS, UCLES, and SONG. The periodogram analysis reveals two periodic signals of approximately 745 and 980 d, associated with planetary companions. A double-Keplerian orbital fit of the data reveals two Jupiter-like planets with minimum masses mb sin i ~ 1.9 MJ and mc sini~ 0.9 MJ, orbiting at semimajor axes of ab ~ 1.75 au and ac ~ 2.15 au, respectively. Given the small orbital separation and the large minimum masses of the planets, close encounters may occur within the time baseline of the observations; thus, a more accurate N-body dynamical modeling of the available data is performed. The dynamical best-fit solution leads to collision of the planets and we explore the long-term stable configuration of the system in a Bayesian framework, confirming that 13% of the posterior samples are stable for at least 10 Myr. The result from the stability analysis indicates that the two planets are trapped in a low-eccentricity 4:3 mean motion resonance. This is only the third discovered system to be inside a 4:3 resonance, making this discovery very valuable for planet formation and orbital evolution models.
Gesehen am 12.02.2020